Zamosc during the Bolshevik invasion in August 1920 - Michnicki, Marcin (City and War, 2021)
November 1918 brought Poland its desired independence. The first serious attempt, which decided about the further existence of the Polish country, was the war with Bolshevik Russia. As part of the 1920 campaign, one of the crucial battles was the battle with the Cavalry army in the Zamosc region, which included the Battle of Komarov and the heroic defence of Zamosc on 29–31 August 1920. The first part of the article presents problems of national, political and economic importance, as well as the identity of patriotic people who lived in the town of Zamosc and its surroundings. It discusses the matter of response to the growing threat of war, which resulted in the escape from the city of clergy and part of the civil and police authorities threatened by siege. The second part of the article focuses on civil-military cooperation during fortification and defence of Zamosc. It also presents the efforts of the civil and military authorities, which tried to prepare the inhabitants of Zamosc for warfare and to organise the life of the city at this difficult time. What is more, it portrays the longer-term consequences of military action for the city and its inhabitants, primarily of an economic aspect.